Experimental induction and oral transmission of avian AA amyloidosis in vaccinated white hens. (June 2013) - Murakami, Tomoaki; Muhammad, Naeem; Inoshima, Yasuo; Yanai, Tokuma; Goryo, Masanobu; Ishiguro, Naotaka
Abstract Avian AA amyloidosis is commonly observed in adult birds afflicted with bacterial infections or chronic inflammatory disorders. Experimental AA amyloidosis in birds can be induced by repeated inflammatory stimulation, such as injection with casein or vaccination with oil-emulsified bacterins. However, the transmission of amyloidosis among avian species has not been studied well to date. In the present study, we confirm the potential induction of avian AA amyloidosis by inoculation of Salmonella enteritidis (SE) vaccine or Mycoplasma gallisepticum vaccine. To determine the transmission of chicken AA amyloidosis among white hens, we induced experimental AA amyloidosis in vaccinated chickens by intravenous or oral administration of chicken AA fibrils. Amyloid deposits were observed in chickens injected with SE and inoculated with chicken AA fibrils intravenously (21/26: 81%) and orally (8/12: 67%). These results suggest that chicken AA amyloidosis can be induced by vaccinations, and may be transmitted among like species by oral administration.